Are We at Home in a Liberal Democracy? Metaphorology and Political Philosophy - Rivera García, Antonio (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
Drawing on both Agnes Heller’s paper “Where Are we at Home?” and Hans Blumenberg’s metaphorology, this article discusses the meaning of the home metaphor as applied to the realm of politics. It examines particularly whether or not liberal democracy can be considered a home. In principle, the article argues that the home metaphor is a better image to think premodern, conservative and communitarian politics. Yet its usage in a liberal context attests to some of the profoundest human anxieties.